Long-term outcomes of platinum-based chemotherapy for T4 stage sinonasal adenoid cystic carcinoma - Song, Xinmao; Sun, Ji; Yang, Gang; Wang, Xiaoshen; Wang, Li (Frontiers in Pharmacology, 2025)
PurposeTo investigate the impact of platinum-based chemotherapy on long-term outcomes of T4 sinonasal adenoid cystic carcinoma (SNACC).MethodsWe retrospectively analyzed clinical data from 87 consecutive patients with T4 SNACC who underwent surgery plus radiotherapy with or without platinum-based chemotherapy in our institution between 1993 and 2019.ResultsOf the 87 cases of T4 SNACC, 57.5% (50/87) of patients underwent platinum-based chemotherapy. Overall, chemotherapy was not associated with overall survival (OS) (P = 0.814), PFS (progression-free survival) (P = 0.508), local recurrence-free survival (LRFS) (P = 0.500) or distant metastasis-free survival (DMFS) (P = 0.202) improvement. Besides, chemotherapy significantly decreased 10-year OS (27.9% vs. 58.8%, P = 0.034) compared with the no-chemotherapy group. Univariate (P = 0.383) and multivariate logistic analyses (P = 0.213) suggested that chemotherapy did not reduce the risk of distant metastasis. Furthermore, multivariate Cox regression analysis indicated that chemotherapy did not improve OS (P = 0.789) or PFS (P = 0.556).ConclusionPlatinum-based chemotherapy did not seem to provide a long-term survival advantage for patients with T4 SNACC and might be associated with worse outcomes after 5 years, although these findings need confirmation through prospective studies.